Love will tear us apart - Seddon, Holly (b)
Kate and Paul have been married for ten years. Childhood best friends who reconnected as adults, Paul now has a high-flying job while Kate looks after their two adorable children. Their friends think they're the perfect couple. Everything should be wonderful. But Kate has a secret. One she's sure Paul doesn't know. Because if he did, would he really love her as much as he says he does? Or would he decide that their life together isn't worth the vow he made all those years ago?
Keywords: Friendship -- Fiction; Man-woman relationships -- Fiction; Psychological fiction